Invers Matriks RLPrFrLcirc (0,…,0,a,a) Ordo n×n Dengan n≥3 Menggunakan Matriks Blok 2×2 - Rahma, Ade Novia; Asyura Nurislam, Asyura; Aryani, Fitri; Marzuki, Corry Corazon (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
[1] H. Anton dan C. Rorres, Aljabar Linear Elementer edisi kedelapan. 2004. [2] B. J. Olson, S. W. Shaw, C. Shi, C. Pierre, dan R. G. Parker, “Circulant matrices and their application to vibration analysis,” Applied Mechanics Reviews, vol. 66, no. 4, 2014. [3] Lin Jiang Z, Ben Xu Z,